Clinical Challenges in Regenerative Endodontic Therapy: A Review - Vivek Thakur (RGUHS Journal of Dental Sciences)
Regenerative endodontic therapy RET has drawn a great deal of interest and is widely recognized because it preserves the function and endurance of teeth. Although it is routinely performed on immature teeth with periapical disease the treatment outcomes remain unpredictable. Instead of producing fibrous connective tissue and amorphous mineral deposits pulp-dentin regeneration should be the real benchmark of RET. Still we have not yet achieved the benchmark of full innervation and vascularization of the generated tissue in the root canal. The main challenges faced with the current clinical protocol of RET are the complete disinfection of root canal space and enhancing pulplike tissue regeneration. This article will address the key challenges and strategies that focus on realizing the goal of regenerative endodontic therapy.